New Records of Biting Midges of the Genus Culicoides (Diptera: Ceratopogonidae) from the Yungas, Paranaense Rainforest and Chaco Ecoregions of Argentina - Veggiani Aybar, Cecilia A. (2012)
Culicoides insignis and C. venezuelensis are documented for the first time from Salta province, C. guttatus from Salta and Tucumán provinces, and C. austroparaensis, C. biestroi, C. fernandoi, and C. foxi from Misiones province. The geographical distributions of C. lahillei, C. brasilianum, C. dureti and C. pseudoheliconiae are extended to Chaco and Misiones provinces.